Key Entry Points for Gender Equity in Energy Access, Energy Policy, Renewable Energy, and Transmission and Distribution - World Bank Group (World Bank, Washington, DC, 2019)
The World Bank is committed to addressing gender equality in energy operations as part of both its new gender strategy and its gender monitoring system,known as the Gender Tag. The World Bank Group Gender Strategy (FY16–23) focuses on four main objectives: (i) Improving Human Endowments; (ii) Removing Constraints for More and Better Jobs; (iii) Removing Barriers to Women’s Ownership and Control of Assets; and (iv) Enhancing Women’s Voice and Agency and Engaging Men and Boys; The Gender Tag asks teams to establish strong links among gender analysis, actions, and monitoring and evaluation. It expects teams to establish a logical results chain to demonstrate how they will address gender gaps identified in the analysis through particular actions, and how they will monitor the progress of these actions. These one-pagers provide hands-on, practical guidance to help task teams close gender gaps in energy operations. They address four energy subsectors—energy access, energy policy, renewable energy, and transmission and distribution—and provide entry points for achieving objectives of the Gender Strategy. The guidance is designed to help task teamsstart the dialogue about how they could close gender equality gaps in their operations both internally as well as with clients. The entry points draw on lessons learned from World Bank energy operations that successfully closed gender equality gaps, as well as from the literature on gender and energy.